Clinical Pharmacokinetics of Brivaracetam: A Systematic Review (Molecular Medicine Communications, 2024)
Brivaracetam (BRV) is an antiepileptic drug (AED) used to treat focal seizures. It can be administered through oral and intravenous (IV) routes. In this review, the main objective is to present a thorough analysis of reported pharmacokinetics (PK) information on BRV in humans. Five electronic databases were used to execute a systematic literature search i.e. Google Scholar, EBSCO, Science Direct, Cochrane, and PubMed. All articles containing information on the PK of BRV in humans were searched. This review process is officially filed in the PROSPERO database under the registration number CRD42023451328. Thirteen papers were finally included in this systematic review after applying eligibility criteria to 1508 publications from all included databases. A dose-dependent increase in Cmax and AUC0-∞ was seen after oral application of BRV. A slight increase in the AUC0-∞ of BRV was observed in severe renal impaired patients as compared to healthy control. The co-administration of BRV with carbamazepine and rifampicin resulted in a significant rise in oral clearance (CL/F) from 0.92 ml/min to 1.30 ml/min and 0.80 ml/min to 1.45 ml/min respectively, emphasizing the importance of medication interactions in clinical settings. The bioavailability and serum half-life (t1/2) of BRV were reduced when administered with drugs. This comprehensive overview not only improves our understanding of the drug's PK behavior but also provides valuable insights for researchers and clinicians to optimize BRV therapy. The presented results may help clinicians understand the PK parameters (AUC0-∞, Cmax, and t1/2) of BRV in foreseeing its adverse drug reactions and drug-drug interactions.
Keywords: Antiepileptic drug; Brivaracetam; Healthy control; Pharmacokinetic; Systematic review; Severe renal impairment